Cyclopentenone prostaglandins suppress activation of microglia: Down-regulation of inducible nitric-oxide synthase by 15-deoxy-Δ(12,14)-prostaglandin J(2) - Petrova, Tatiana V. (The National Academy of Sciences, 1999)
Mechanisms leading to down-regulation of activated microglia and astrocytes are poorly understood, in spite of the potentially detrimental role of activated glia in neurodegeneration. Prostaglandins, produced both by neurons and glia, may serve as mediators of glial and neuronal functions. We examined the influence of cyclopentenone prostaglandins and their precursors on activated glia. As models of glial activation, production of inducible nitric-oxide synthase (iNOS) was studied in lipopolysaccharide-stimulated rat microglia, a murine microglial cell line BV-2, and IL-1β-stimulated rat astrocytes. Cyclopentenone prostaglandins were potent inhibitors of iNOS induction and were more effective than their precursors, prostaglandins E(2) and D(2). 15-Deoxy-Δ(12,14)-prostaglandin J(2) (15d-PGJ(2)) was the most potent prostaglandin among those tested. In activated microglia, 15d-PGJ(2) suppressed iNOS promoter activity, iNOS mRNA, and protein levels. The action of 15d-PGJ(2) does not appear to involve its nuclear receptor peroxisome proliferator-activated receptor γ (PPARγ) because troglitazone, a specific ligand of PPARγ, was unable to inhibit iNOS induction, and neither troglitazone nor 15d-PGJ(2) could stimulate the activity of a PPAR-dependent promoter in the absence of cotransfected PPARγ. 15d-PGJ(2) did not block nuclear translocation or DNA-binding activity of the transcription factor NFκB, but it did inhibit the activity of an NFκB reporter construct, suggesting that the mechanism of suppression of microglial iNOS by 15d-PGJ(2) may involve interference with NFκB transcriptional activity in the nucleus. Thus, our data suggest the existence of a novel pathway mediated by cyclopentenone prostaglandins, which may represent part of a feedback mechanism leading to the cessation of inflammatory glial responses in the brain.